'Give People What They Expect': John Hughes' Family Films and Seriality in 1990s Hollywood. Issue 1 (1st October 2017) - Chard, Holly
Abstract : This article explores serial production strategies and textual seriality in Hollywood cinema during the late 1980s and early 1990s. Focusing on John Hughes' 'high concept' family comedies, it examines how Hughes exploited the commercial opportunities offered by serial approaches to both production and film narrative. This article first considers why Hughes' production set-up enabled him to standardise his movies and respond quickly to audience demand. The analysis then explores how the Home Alone lms (1990–97), Dennis the Menace (1993) and Baby's Day Out (1994) balanced demands for textual repetition and novelty.